Model for Predicting the Hydraulic Conductivity of Frozen Soils Using the Soil Freezing Characteristic Curve - Hao Wang; Sai K. Vanapalli (Water Resources Research)
Abstract Frost heave and thaw settlement driven by freeze‐thaw cycles in seasonally frozen soils of cold regions are strongly related to water migration. A key parameter controlling water migration in frozen soils is the hydraulic conductivity, which predominantly governs the movement of water under thermal and hydraulic gradients. The direct measurement of hydraulic conductivity in frozen soils requires extensive laboratory equipment, is time‐intensive and hence expensive. To address these challenges, numerous prediction models have been proposed in the literature utilizing the Soil Freezing Characteristic Curve (SFCC). However, many of these models suffer from limitations associated with computationally intensive integral formulations that only address capillary water flow and ignore the contribution of film water flow—a critical mechanism driving frost heave. In this study, a novel closed‐form model is proposed for predicting the hydraulic conductivity in frozen soils based on a theoretical framework using the capillary bundle model and the SFCC. Validation against published experimental data for a variety of soil types demonstrates the strong predictive capability of the proposed model. The model is robust and can be used for estimating water movement in frozen soils, offering significant advantages for use in the numerical simulations of frost heave, artificial ground freezing, and other cold region engineering applications.